A PARAMETRIC STUDY AND PERFORMANCE EVALUATION OF DC ELECTROMAGNETIC PUMPS WITH BEMC-1 CODE - Braz Filho, F. A.; Guimarães, L. N. F.; Borges, E. M. (Revista de Engenharia Térmica, 2006)
Electromagnetic pumps are used to control liquid metal fluid flow in cooling loops. The principle of operation of an electromagnetic pump is based on Lorentz’s force. This is obtained by interaction of the magnetic field and the electrical current, imposed and adjusted by independent external electric power sources. In this work are presented the continuous current electromagnetic pumps, their basic equations and the BEMC-1 code, developed for design and performance evaluation of a DC electromagnetic pump. The main objective of this paper is a parametric study for magnetic induction, static pressure, fluid flow and performance evaluation of the pump. The theoretical results are compared with the experimental data to get adjust factors to be used in the BEMC-1 code. In this way the BEMC-1 code can be validated and used in the evaluations and projects of DC electromagnetic pumps.